PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR MATEMATIKA KELAS XI IPA SMA NEGERI 1 SUTERA - Deni Indra Yuri (Departemen Matematika, 2021)
Matematics learning outcomes are an important component and must be achieved in learning mathematics. The result of the observation show that the mathematics learning outcomes of students at SMA Negeri 1 Sutera still low. Therefore, research was carried out in order to improve students mathematics learning outcomes by adjusting the group investigation (GI) type of cooperative learning model. The type of research used was quasy experimental and descriptive with randomized control group only design. Based on the research result, it can be concluded that the development of students mat learning outcomes hematics learning outcomes during the learning process using the group investigation (GI) type of cooperative learning model has increase, and the mathematics of students whose learning process uses the group investigation (GI) type of cooperative learning model are better than the result. Learn mathematics students who learn with conventional learning. Keywords — Mathematical Learning Outcomes Cooperative Learning Model Group Investigation (GI).